Efficacy of thymosin alpha-1 as an immunomodulatory adjuvant in patients with recurrent implantation failure: a real-world retrospective analysis - Joshi, Ranjit; Patil, Sheetal Yogesh; Gawale, Sachin; Parekh, Prathmesh; Dhakare, Trupti Jugansingh; Salunke, Nitin; Agarwal, Rajeev (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: Recurrent implantation failure (RIF) remains a major challenge in assisted reproductive technology (ART), affecting approximately 10–15% of couples undergoing treatment. Immune dysregulation is considered an important contributor to implantation failure. Thymosin Alpha-1, an immunomodulatory agent, has shown promising results in difficult-to-treat infertility cases. This study evaluated the real-world effectiveness of Thymosin Alpha-1 as an adjuvant therapy in patients with RIF in an Indian clinical setting. Methods: This retrospective, observational study was conducted at a private infertility center in India. Medical records of adult women aged over 30 years diagnosed with RIF over a one-year period were analyzed. All included patients received Thymosin alpha-1 (1.6 or 3.2 mg daily or on an alternate-day regimen) for a minimum of 118 days. Demographic characteristics, comorbidities, infertility-related conditions including polycystic ovary syndrome (PCOS), endometrial features, immunological parameters, treatment regimens and outcomes were evaluated. Results: Most patients were aged 31–35 years (41.1%), followed by 36–40 years (25.6%). Thyroid disorders (5.6%) and diabetes (2.2%) were uncommon, while 82.2% had no comorbidities; latent tuberculosis was present in 13.3%. Anovulatory cycles were observed in 17.8% of patients and 71.1% had a thin endometrium. Immunological parameters showed marked variability, including mean CD16+56 natural killer cell counts of 175±103 cells/µl and mean TNF-α levels of 18.4±41.2 pg/ml. PCOS was identified in a subset of patients. All patients with RIF (n=90) who received thymosin alpha-1 therapy for at least 118 days demonstrated positive reproductive outcomes, regardless of dosing regimen. Conclusions: Thymosin alpha-1 therapy was associated with encouraging outcomes in patients with RIF, supporting its role as an effective immunomodulatory adjuvant.